Perancangan dan Implementasi Sistem Keamanan Kendaraan Berbasis IoT Menggunakan ESP32, FastAPI, dan Aplikasi Android - Rahman, M Abdur; Simanjuntak, Noe Prihartoyo; Pratama, Adi Nuzul; Stelyven, Stelyven; Yulianto, Andik (Universitas Internasional Batam, 2025)
The advancement of digital technology has made a major contribution to improving security systems, especially in the automotive sector. One of the main challenges in securing motor vehicles is providing real-time protection against potential threats such as theft or vandalism. In this study, an Internet of Things (IoT)-based vehicle security system was designed and implemented that utilizes the ESP32 microcontroller as the main tool to detect physical contact or interference with the vehicle. This system integrates the MQTT communication protocol for sending data to a FastAPI-based backend server, which then stores the data in MongoDB Atlas and sends notifications to users via Firebase Cloud Messaging (FCM). Users can monitor and respond to these notifications through an Android application built using Android Studio and the Java programming language. In addition to notifications, this application also provides a sound alarm player feature and a display of sensor activity history. The test results show that the system is able to detect and respond to events quickly and accurately, with a notification delivery time of less than two seconds after the data is received by the server. With an integrated and real-time system architecture, this solution is expected to be an economical, efficient, and reliable alternative to improve the security of private and public vehicles.